International capital flows and bond risk premia - Jesus Sierra (Bank of Canada, 2010)
This paper studies the impact of international capital flows on asset prices through risk premia. We investigate whether foreign purchases of U.S. Treasury securities significantly contributed to the decline in excess returns on long-term bonds between 1995 and 2008. We run forecasting regressions of realized excess returns on measures of net purchases of treasuries by both foreign official and private agents. We find a clear distinction in the effects of flows on excess returns. Official flows, with a negative and non-linear effect, appear similar to relative supply shocks; private net purchases, with a positive and linear effect, resemble flows that absorb excess supply and are thus compensated in equilibrium for this service, similar to the role of arbitrageurs in preferred-habitat models of the term structure.
Keywords: G11; G12; G15; F31; F32; F34; C22; 330; Financial markets; Internationaler Finanzmarkt; Kapitalmobilität; Kapitalanlage; Risikoprämie; Kapitalertrag; USA